Corona, Risk at Work, Rethinking in the Role of State - Bahram Akhavan kazemi; Fatemeh Forootan (دولت‌پژوهی, 2023)
The main issue of this article is about the relationship of work and Coronavirus and the changes and transformations that have been created in the field of work due to the occurrence of this global risk and, as a result, have transformed the role of the government; changes that, according to Ulrich beck's interpretation, by removing the standards and certainties of work, such as working in a specific place as a factory or an office and during specific hours of the day, have caused the destandardization of work and turned the global society into a risk global society and caused citizens to rethink the internal and international role of governments. Indeed, Coronavirus By forcing governments to adopt policies such as quarantine, forced suspension of jobs, limiting social interactions and reducing relations with other countries not only led to the closure of many businesses and unemployment of many people, but also by creating the need for a decisive role of the government in order to support different classes of different societies around the world to deal with this pandemic, it widened the scope of government's influence and the field of its social interventions. So, according to the findings of the research, which are the result of documentary studies by using the historical-adaptive approach to compare two different types of government in China and the United States, it can be inferred that with the outbreak of Corona, the liberal model of government is being replaced by a stronger government that is not a type of Chinese authoritarianism, but is an embedded liberalism that combines economic freedom with domestic social support. Some Important works have been written about the political and social consequences of Corona, among which we can mention Francis Fukuyama's article (2020) entitled "Pandemic and Political Order". The author claims that this crisis, like other global crises such as: The Great Recession, World Wars, the 11th September attack, has special consequences which its political dimensions are even more important than its economic effects; Therefore, this pandemic can lead to the intensification of nationalism, isolationism and an attack to the liberal political order. Farhad zivyar and reza khodabandelou(2019) in an article entitled " corona and reproduction of authoritarianism in democratic states" claim that successful experience of authoritarian states such as china in dealing with coronavirus can turn the global desire in to the accumulation and concentration of power and therefore, the closure of democratic space. But what distinguishes this article from other works that have been written in this field is its focus on the work and risks that have occurred in this arena by the occurrence of Corona that has changed the citizen's attitude about the role of government and the philosophy of its existence. In addition, although these works give priority to authoritarian states in drawing the political order of the post-coronavirus world, in this article, authoritarianism has its own criticisms that reveal the necessity of moving towards a middle path in the frame of embedded liberalism. So, it can be concluded that although since four decades ago, the best government is the one that restricts its field of intervention in society and only provides military security in the country, but in the risk situation, not only governments have found an opportunity to expand their interventions in the society, but also citizens have come to the conclusion that their egalitarianism concerns and their comprehensive security may be more important than their liberal desires. So, they prefer governments that deal with this pandemic and its harmful effects in different aspects with a wider range of power. The weak performance and inefficiency of the United States of America as the leader of the neoliberal agenda of the role and duties of the government on the one hand and the success of Chinese authoritarianism in dealing with this pandemic, verifies the accuracy of this matter. Of course, it does not mean that the Chinese authoritarian system is uncritical and perfect and its acceptance by other countries in the post-corona world is inevitable; Because China, due to the special features of its political system, such as complete controlling the flow of information, may be condemned of intervening the private sphere and totalitarianism. Therefore, it seems that balance is a requirement of dynamism, and this dynamism can be seen in the performance of Denmark government, which seeks to create a balance between international economic freedom and domestic social protection. So it's possible that the political order in the post-Corona world should be based on an embedded liberalism that maintains its economic independence and stands on its own feet in the international arena despite being affected by the flow of global communications and exchanges.